Market Study for Thailand : Plastics Circularity Opportunities and Barriers - World Bank Group (World Bank, Washington, DC, 2021)
Plastics are an integral and important part of the global and Thai economies. Since the 1950s the use of plastic products has expanded twenty-fold owing to their low cost, various functional properties, durability and wide range of applications. Mismanaged plastic waste from land-based sources, especially in the form of packaging, generates significant economic costs globally and in Thailand by reducing the productivity of vital natural systems and clogging urban infrastructure. The private sector can lead the transition from current take-make-waste linear models to circular economy approaches in collaboration with the public sector and other stakeholders. This report focuses on the market assessment of plastics value chains and the recycling market in Thailand with the overall goal of identifying the opportunities and barriers for plastics circularity in the country.